A new prediction model for left ventricular systolic function recovery after catheter ablation of atrial fibrillation in patients with heart failure and reduced ejection fraction, The ANTWOORD Study. (19th May 2022) - Bergonti, M; Spera, F; Tijskens, M; Bonomi, A; Saenen, J; Huybrechts, W; Miljoen, H; Wittock, A; Casella, M; Tondo, C; Heidbuchel, H; Sarkozy, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In patients with heart failure with reduced ejection fraction (HFrEF) and atrial fibrillation (AF), pulmonary vein isolation (PVI) improves left ventricular ejection fraction (LVEF), along with prognosis, in a variable percentage of patients. Aim: To investigate the predictors of LVEF recovery after PVI and to develop a prediction model for individualized assessment. Methods: We conducted an observational, retrospective, single-center study on 111 consecutive patients with AF and HFrEF undergoing PVI. Patients were divided into Responder vs. Non-Responder according to the "Universal definition of HF". Clinical predictors were evaluated by multivariate logistic regression analysis and cross-validation technique. Independent predictors were used to build an internally validated prediction model. Results Responders (54%) had significantly shorter QRS duration and less dilated left atria. Persistent AF and absence of a known etiology more frequent among Responders. AF recurrence was non-significantly different between the two groups (p=0.2), although clinical AF burden was lower in Responders, after PVI (p<0.001). Absence of known etiology, presence of persistent AF, left atrial volume index<50ml/m2, and QRS<120msec were independent predictors of LVEF recovery and composed the "Antwerp Score". Patients with Antwerp Score ≤1 had 90% likelihood of LVEF recovery, compared to 5% in patients with 3-6. Conclusions Patients with wide QRS complex, known HF etiology, dilated left atria, and paroxysmal AF were less likely to recover LVEF after PVI. A new score system based on the above-mentioned parameters adequately predict LV function recovery after PVI. These results warrant confirmation and prospective validation.